Soccer players have a better standing balance in nondominant one-legged stance - Barone, R.; Macaluso, F.; Traina, M.; Leonardi, V.; Farina, F.; Di Felice, V. (Open Access Journal of Sports Medicine, 2011)
The purpose of this study was to analyze the differences in standing balance during dominant and nondominant one-legged stance among athletes of different sports and sedentary subjects. The right-footed subjects of four groups (sedentary, n = 20; soccer, n = 20; basketball, n = 20; windsurfer n = 20) underwent 5-sec unipedal (left and right foot) stabilometric analysis with open eyes and closed eyes to measure center of pressure (COP) sway path and COP velocity (mean value, anteroposterior, and laterolateral in millimeters per second). The soccer group showed better standing balance on the left leg than the sedentary group (P < 0.05). No other significant differences were observed within and amongst groups. The soccer players have a better standing balance on the nondominant leg because of soccer activity.